Hubungan Kepadatan Limfosit Intratumoral dan Tipe Histopatologik Karsinoma Tiroid di Departemen Patologi Anatomik FKUI/RSCM - Kamarudy Lay, Fanny; Stephanie Harahap, Agnes; Francisca Ham, Maria (Majalah Patologi Indonesia, 2023)
Background The presence of tumor-infiltrating lymphocytes (TILs) has been widely explored as one of the factors that can affect the success of immunotherapy in various cancers. This study aims to investigate the TILs in various types of thyroid carcinoma (TC) and its association with the aggressive histopathological type compared to the less aggressive histopathological type of TC. Methods The population covered by this retrospective study was TCs diagnosed at the Department of Anatomic Pathology, Faculty of Medicine, University of Indonesia/Dr. Cipto Mangunkusumo National Central General Hospital, period 2015-2019. The research sample was divided into group of TCs with aggressive histopathological type and less aggressive histopathological type with a total of 25 samples for each group. TILs was calculated in 10 high power fields (HPF) with 400 kali magnification. The analyses were conducted using Mann-Whitney and Kruskal Wallis test. Results TILs count was found with a median value of 43 (3-660) in the aggressive histopathological group and 36 (9-387) in the less aggressive histopathological group (p:0.96, CI:95%). The highest TILs was found in anaplastic thyroid carcinoma (ATC) and papillary thyroid carcinoma (PTC) with anaplastic components. TILs count was also found with a median value of 17.5 (3-75) in male and 48 (9-660) in female (p:0.02, CI:95%). Conclusion There was no significant association between TILs and histopathological types of TC (aggressive and less aggressive). However, there is a tendency for high TILs in ATC and PTC with anaplastic components. There is also a significant difference in TILs between male and female gender.